WDM technologies - Dutta, Achyut K.; Dutta, N. K. (Niloy K.), 1953-; Fujiwara, Masahiko (Amsterdam ; Boston : Academic Press, 2002)
This book will be an excellent resource for engineers and researchers engaged in all aspects of fiber optics communication, such as, optoelectronics, equipment/system design, and manufacturing. The book is also a resource for graduate students and scholars interested in these rapidly growing fields. Provides the reader with insight and understanding for key active optical components frequently being / to be used in the optical communication systems, essential building blocks of today's/next generation fiber optic networks Allows engineers working in optical communication area, (from system to component) to understand the principle and mechanics of each key component they deal with for optical system design Covers different laser diodes as transmitter and pumping sources, different modulators, and different photodetectors.
[v. 1]. Active optical components -- v. 2. Passive optical components.
Includes bibliographical references and indexes.
Keywords: Wavelength division multiplexing; Optical communications; Optoelectronic devices; Electronic books